Daughters from Good Families and their Seals in the Old Babylonian Period - Colbow, Gudrun (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Daughters from socially high-ranking or royal families were precious in the Old Babylonian societies. They could be married off to forge internal and external alliances or could be placed as priestesses in temples. The women in the priesthood obviously were wealthy, because they received large dowries from their families and no husband could make a determination of the riches they owned. They were of the same contractual capability as the men and leased, sold and bought houses, plots and fields, adopted heirs as long as they were not allowed to have children and arranged heritage contracts. As precious as the rest of their possessions were their seals.